A History of Reading - (:unkn) unknown (TURKISH LIBRARIANS ASSOC, 2015)
The meaning of reading according to Alberto Manguel is to have the art of giving life to a message which comes from past to today. Reading is the objective/intellectual context of starting up and shutting the time. Reading is an open ended tool that makes it possible to know the words/thoughts which spoke to humanity from long time ago. The books/libraries offer a way to look at the nature, understand history, live and interpret the life. In other words,, the books/libraries are natural spaces of the freedom of opinion. The reading action is a great need to redefine the Universe, realize miracles, oppose injustice. In essence, the life is focused on the reader from the beginning of transferring the words by writing. The history of reading started when the first writer drew and gave voice to the first letters. In brief, the history of reading is considered as the reading action within a wide context. Now, we know there is a history of the reading.